2018
DOI: 10.1007/s11892-018-1036-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress Hyperglycemia in Patients with Tuberculosis Disease: Epidemiology and Clinical Implications

Abstract: Among patients with TB disease, the development of stress hyperglycemia may influence the clinical manifestation and treatment response of some patients and can complicate diabetes diagnosis. Research is needed to elucidate the relationship between TB disease and stress hyperglycemia and determine the extent to which stress hyperglycemia impacts TB treatment response. Currently, there is insufficient data to support clinical recommendations for glucose control among patients with TB disease, representing a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 90 publications
1
26
0
1
Order By: Relevance
“…Of those who did not report a diabetes diagnosis, 29% still had elevated RBG. Incident TB is associated with hyperglycemia that may resolve over the course of TB treatment independent of diabetes interventions, but may also be a prognostic marker of poor short-term outcomes and longer-term elevated risk of diabetes [6, 2932].…”
Section: Discussionmentioning
confidence: 99%
“…Of those who did not report a diabetes diagnosis, 29% still had elevated RBG. Incident TB is associated with hyperglycemia that may resolve over the course of TB treatment independent of diabetes interventions, but may also be a prognostic marker of poor short-term outcomes and longer-term elevated risk of diabetes [6, 2932].…”
Section: Discussionmentioning
confidence: 99%
“…1 There is evidence that the presence of clinical TB disease drives stress hyperglycaemia, impacting on clinical outcomes and response to treatment. 16 As rates of diabetes continue to rise, and the TB epidemic continues, there is a pressing need for bidirectional screening in countries facing the double burden of TB and diabetes. Work in India has shown success at screening newly diagnosed TB cases for diabetes, 17 due to the availability of a simple screening blood test (HbA1c) and the use of existing systems established to screen TB cases for HIV.…”
Section: Diabetes and Specific Infectionsmentioning
confidence: 99%
“…Sepsis-related hyperglycaemia may be a risk factor for future development of T2DM, 101 and stress hyperglycaemia induced by chronic infections such as TB may contribute to the global burden of diabetes. 16…”
Section: Mechanisms Of Increased Susceptibility To Infection In Diabetesmentioning
confidence: 99%
“…A study in Tanzania observed a stronger TB/DM association among people living with HIV [ 13 ], while another Tanzanian study observed stronger TB/DM association in HIV-1–uninfected persons (OR, 4.2 [95% CI, 1.5–11.6]) compared with people living with HIV (OR, 0.1 [95% CI, .01–1.8]) [ 14 ]. These 3 diseases interact, with the potential to influence risk of disease and prognosis and to complicate clinical management [ 15 ].…”
mentioning
confidence: 99%